Do differences in muscle recruitment between novice and elite cyclists reflect different movement patterns or less skilled muscle recruitment? - Chapman, A.; Vicenzino, B.; Blanch, P.; Hodges, P. (Journal of Science and Medicine in Sport, 2009)
It has been shown that novice and elite cyclists use different patterns of leg muscle recruitment when cycling. These differences may reflect less skilled muscle recruitment by novice cyclists or different, but not necessarily less skilled, movement patterns. We compared kinematics of the pelvis and lower limbs and leg muscle activity during cycling between novice and elite cyclists, to determine if differences in leg muscle activity are associated with differences in movement patterns. Three-dimensional pelvic and lower limb kinematics and electromyographic (EMG) activity of leg muscles were measured during cycling at 55-60, 75-80, 90-95 rpm and preferred cadence. Differences were found between novice and elite cyclists in the recruitment of leg muscles, which were consistent with previous findings. Joint-angle and velocity were not different between groups. Absolute range of sagittal plane motion of the ankle was less in novice cyclists than in elite cyclists. Cadence did not influence kinematics. Coordination of sagittal plane motion of the hip and ankle, and knee and ankle, was stronger in elite cyclists. Furthermore, coordination of these movements was more consistent between pedal strokes in elite cyclists. Individual variance of kinematics was not different between groups. We conclude that differences in leg muscle recruitment between novice and elite cyclists may be explained in part by small kinematic variations at the ankle, i.e. less absolute range of motion, but contend that differences in muscle recruitment are primarily a reflection of more skilled muscle recruitment by elite cyclists.